Identifying age penalty in women’s wages: new method and evidence from Germany 1984-2014 - Foundation of Admirers and Mavens of Economics, Warsaw; Tyrowicz, Joanna; van der Velde, Lucas; van Staveren, Irene (Warsaw, 2017)
"Given theoretical premises, gender wage gap adjusted for individual characteristics is likely to vary over age. We adapt DiNardo, Fortin and Lemieux (1996) semi-parametric technique to disentangle year, cohort and age effects in adjusted gender wage gaps. We rely on a long panel of data from the German Socio-Economic Panel covering the 1984-2015 period. Our results indicate that the gender wage gap increases over the lifetime, for some birth cohorts also in the post-reproductive age."